METHOD OF DETERMINATION OF GENERAL LEVEL OF IRRADIATION OF PERSONNEL IN MODERN INFORMATION SPACE - Конахович, Г. Ф.; Одарченко, Р. С.; Конахович, Г. С.; Карпов, А. В. (Science-based technologies, 2010)
This topic describe main types of electromagnetic radiation, which influence on the vital functions of people. Was designed the method of determination of general level of irradiation of personnel on workplaces and in resting-places. We calculated indexes which determine harmfulness of electromagnetic radiation of different frequency ranges.